Prevalence of fascoliasis in sheep and cattle in the province of Pataz, La Libertad, Peru through coproparasitological tests and Western Blot - Jara Campos, César (2018)
The aim of this study was to determine the prevalence of fascioliasis in sheep and cattle in five districts of the Province of Pataz, La Libertad, Peru, through coprological tests and Western blot. The study was a prospective cross-sectional type. Faecal and blood samples from 388 sheep and 365 cattle were evaluated from the districts of Buldibuyo, Chillia, Huaylillas, Taurija and Urpay, between April and October 2015 by the methods of formalin-ether and Kato Katz and Western Blot. Results showed than 61.8% of sheep and 86.8% of cattle presented anti-Fasciola hepatica antibodies (positive serology) and 42.3% of sheep and 62.4% of bovines presented eggs of F. hepatica in faeces (positive coprology). The districts of Buldibuyo, Chillia and Huaylillas presented the highest prevalence of fascioliasis in both ovine and bovine. It is concluded that the province of Pataz can be considered hyperendemic zone to fasciolosis by Fasciola hepatica.